Implementasi Shariah Governance di Bank Syari’ah - Faozan, Akhmad (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Shariah governance is a combining between the theory of Good Corporate Governance and the theory of sharia compliance in sharia bank. Then, Good Corporate Governance is a system of banking management which manages, operates and supervises the process of effort control to rise the added value and as a form of giving attention to the stakeholders. Whereas shariah compliance is a sharia bank?s compulsory to fulfill the obedience toward shariah?s principle. The implementation of shariah governance in shariah bank is based on five (5) principles which they are the transparency, accountability, responsibility, professionalism, and normality or fairness. Whereas shariah bank in its shariah compliance?s implementation, there are should be no usury (riba), uncertainty (gharar), and gambling (maysir) in all its transactions, operates the business which bases on halal (permissible by the shariah) profit, runs the mandate which was given by the customer to the bank, manages zakat (wealth„s purification), infaq (spending in Allah?s way), and sadaqah (alms) in trusted way.